2012
DOI: 10.1002/anie.201207803
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation of Amides to Amines under Mild Conditions

Abstract: Under (not so much) pressure: A general method for the hydrogenation of tertiary and secondary amides to amines with excellent selectivity using a bimetallic Pd–Re catalyst has been developed. The reaction proceeds under low pressure and comparatively low temperature. This method provides organic chemists with a simple and reliable tool for the synthesis of amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 36 publications
3
76
0
Order By: Relevance
“…A 1 H− 13 C HMQC experiment revealed a correlation between this signal and a 13 C NMR signal at 55.1 ppm. A DEPT-135 experiment indicated that the signal is from a CH 2 group.…”
Section: Acs Catalysismentioning
confidence: 84%
See 1 more Smart Citation
“…A 1 H− 13 C HMQC experiment revealed a correlation between this signal and a 13 C NMR signal at 55.1 ppm. A DEPT-135 experiment indicated that the signal is from a CH 2 group.…”
Section: Acs Catalysismentioning
confidence: 84%
“…In addition, hydrodeoxygenation of primary and secondary amines often yields mixtures resulting from alkyl group disproportionation. 3,13,17,18 Although a range of late metal complexes have been reported to efficiently reduce amides through hydrosilylation, 8,9,19 new catalytic processes are still needed to address the challenges facing amide deoxygenations (Scheme 1). Few catalytic systems are able to effectively reduce primary, secondary, and tertiary amides, 11 and few catalysts are based on metal complexes other than nonoxophilic late metals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Attention has been attracted to the hydrogenation of crotonaldehyde to crotyl alcohol in aqueous solution for the development of safer and greener process [12]. In addition, water would be generated in many hydrogenation reactions [13]. For example, the hydrogenation of nitrobenzene to aniline produces great amount of water [14].…”
Section: Introductionmentioning
confidence: 99%
“…Turnovers in 1 h can be as high as 1500 with linearities up to 98.5%. 30 Using our catalytic system under similar conditions to those employed by Drent in toluene, one of Drent's favoured solvents, no conversion was obtained when using a catalyst loading of 0.2 mol% either with aniline or the more nucleophilic 15 in the absence of 2-naphthol ( Table 2, entries 1 and 2), but significant activities (31% conversion for aniline ( (11). e N-phenyl 3-methylhexanamide (12).…”
Section: -Naphthol and Nai As Promotersmentioning
confidence: 88%